A numerical and experimental study through laser thermography for defect detection on metal additive manufactured parts (Fracture and Structural Integrity, 2017)
Additive manufacturing has been recently employed in industrial sectors with the fundamental requirement for zero defect parts. Technological developments in additive manufacturing notwithstanding, there continues to be a scarcity of non-destructive inspection techniques to be exploited during the manufacturing process itself, thus limiting industrial advancements and extensive applications. Therefore, being able to integrate the defect inspection phase within the additive manufacturing process would open the way to enabling corrective actions on the component in itinere, that is, before reaching the final product. For this reason, new methods of in-process monitoring are gaining more and more attention nowadays. In this work, a remote laser thermographic methodology is employed as a mean to detect micrometric defects in additive manufactured samples. Beforehand, a preliminary Finite Element Analysis was carried out in order to optimize the sensitivity of the technique to the micrometric defects. Our results indicate that the technique is proved to be quite successful in detecting flaws, with the added plus of being suitable for integration in the additive manufacturing equipment, thus allowing a continuous in-line inspection.
Keywords: Non-destructive testing; IR Thermography; Additive Manufacturing; Laser Thermography; FEA; Modeling